EARLY PREVENTION OF METABOLIC DISORDERS AND THEIR MICROALBUMINURIA - Deekshith Battu (Journal of Science in Medicine and Life, 2024)
. our research was carried out in family clinics in the city of Samarkand (Uzbekistan). The study involved 55 people aged 7 to 18 years (average age of children 12.03±0.17 years), with overweight and obesity. The control group included 20 practically healthy children with normal body weight and no pathology of the musculoskeletal system. Anthropometric studies were carried out using standard measuring instruments (floor height meter and medical scales). Anthropometric measurements include: height, body weight, waist and hip circumference. Comparison of the obtained data and assessment of physical development were carried out using the WHO cumulative centile tables of age and gender distribution of height and body weight for children 5-19 years old [1]. Body mass index (BMI) was calculated from the measurements. Outcomes were assessed using BMI standard deviations (SDS) according to WHO recommendations [1]. Obesity in children and adolescents should be defined as +2.0 SDS BMI